Gender Differences in Language of Standardized Letter of Evaluation Narratives for Emergency Medicine Residency Applicants. Issue 4 (19th September 2017) - Li, Simiao; Fant, Abra L.; McCarthy, Danielle M.; Miller, Danielle; Craig, Jill; Kontrick, Amy
Abstract: Objective: While gender differences in language for letters of recommendation have been identified in other fields, no prior studies have evaluated the narrative portion of the emergency medicine (EM) standardized letter of evaluation (SLOE). We aim to examine the differences in language used to describe male and female applicants within the SLOE narrative. Methods: Invited applicants to a 4‐year academic EM residency program within a single application year with a SLOE were included in the sample. Exclusion criteria were SLOE of applicants from non–Liaison Committee on Medical Education (LCME) schools or first rotation SLOE not available for download. Data were collected on applicant gender, age, rotation grade, Alpha Omega Alpha designation, and medical school rank. The previously validated Linguistic Inquiry and Word Count (LIWC) program was used to analyze frequency of words within categories relevant to letters of recommendation. Descriptive statistics, t‐tests, and chi‐square tests were employed in analysis. Results: Of 1, 025 applicants within a single application year, 265 were invited to interview; 237 applicants had a first rotation SLOE available for analysis. There were no differences between male and female applicants for baseline characteristics. The median word count per SLOE narrative was 199; within the LIWC dictionary and user‐defined categories, words within the categories of affiliation and ability appeared more frequently for female applicants. Conclusions: Our results with respect to the SLOE narrative reinforce prior research that letters of recommendation for female applicants highlight communal characteristics of teamwork, helpfulness, and compassion. Contrary to prior research, ability words highlighting intelligence and skill appeared with greater frequency for female applicants. No pervasive differences were found in other word categories. In this sample, the standardized format of the SLOE resulted in letters that were relatively free of gender bias.